Avaliação em enfermagem de pessoas com úlceras cutâneas por pênfigo vulgar - Costa, Mariana Takahashi Ferreira [UNIFESP] (2016)
It is essential to enunciate the nursing assessment of people with pemphigus vulgaris skin ulcers under the lens of dermatology. The disease, although considered rare, has a high prevalence in Brazil. This study aims to unveil the nursing assessment of people with pemphigus vulgaris in the light of dermatology. Method: This is a descriptive and exploratory study conducted in four stages: an integrative literature review, characterization of pemphigus skin ulcers according to skin elementary lesions, natural history of the disease and nursing care for people with pemphigus vulgaris and finally the clinical analysis of a number of cases. The dependent variable was the presence of the ulcer and the independent variables were elementary lesions and clinical criteria such as pain and skin epithelialization. The data were analyzed descriptively. Results: The results allowed us to analyze: 1. the studies evaluating the ulcers were performed with medical focus and the nomenclature used to describe pemphigus skin ulcers according to the level of evidence of the studies was based on elementary lesions, i. e. update and validation studies in the light of dermatological glossary: color changes: vascular and blood stains, described in the studies as new erythema; pigmentary spots: post-inflammatory hyperpigmentation; fluid collections: blisters and bubbles; thickness changes and tissue loss - erosion, eroded areas, erosive lesions, crust and epithelialization. The disease natural history describes the nursing assessment for patients? comfort and allows the implementation of a clinical intervention with satisfactory results on pain control and ulcer epithelialization. Conclusion: The standardization of the nomenclature used to describe the skin ulcers in pemphigus is a tool that allows a safer patient care. The low level of evidence of the studies points to the need to conduct controlled studies to corroborate the best nursing practice in dermatology.